Condom use at last sex by young men in Ethiopia: the effect of descriptive and injunctive norms - Jain, Aparna (Reprod Health, 2018)
BACKGROUND: Condoms are an important prevention method in the transmission of HIV and sexually transmitted infections as well as unintended pregnancy. Individual-level factors associated with condom use include family support and connection, strong relationships with teachers and other students, discussions about sexuality with friends and peers, higher perceived economic status, and higher levels of education. Little, however, is known about the influence of social norms on condom use among young men in Ethiopia. This study examines the effect of descriptive and injunctive norms on condoms use at last sex using the theory of normative social behavior. METHODS: A cross-sectional survey was implemented with 15-24 year old male youth in five Ethiopian regions in 2016. The analytic sample was limited to sexually active single young men (n = 260). Descriptive statistics, bivariate and multivariate logistic regressions were conducted. An interaction term was included in the multivariate model to assess whether injunctive norms moderate the relationship between descriptive norms and condom use. RESULTS: The descriptive norm of knowing a friend who had ever used condoms significantly increased respondents’ likelihood of using condoms at last sex. The injunctive norm of being worried about what people would think if they learned that the respondent needed condoms significantly decreased their likelihood to use condoms. The injunctive norm did not moderate the relationship between descriptive norms and condom use. Young men who lived closer to a youth friendly service (YFS) site were significantly more likely to have used condoms at last sex compared to those who lived further away from a YFS site. CONCLUSIONS: Social norms play an important role in decision-making to use condoms among single young men in Ethiopia. The interplay between injunctive and descriptive norms is less straightforward and likely varies by individual. Interventions need to focus on shifting community-level norms to be more accepting of sexually active, single young men’s use of condoms and need to be a part of a larger effort to delay sexual debut, decrease sexual violence, and increase gender equity in relationships.